PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN TIPE STUDENT TEAM ACHIEVEMENT DIVISION SISWA SEKOLAH DASAR - Peronika, Aneti; Sugiyono, Sugiyono; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "Whether using Student Team Achievement Division type can improve the learning result of Social Sciences of VA class of State Elementary School 04 Bengkayang Bengkayang Sub-district of Bengkayang Regency". This study aims to improve the learning of Social Sciences using the type of Students Teams Achievement Division. This research uses descriptive method with form of research of class action and is collaborative. The place of research took place at State Elementary School 04 Bengkayang with subject of research that is student of class V A which amounted to 36 people. Technique of collecting data that is used is direct observation technique with data collecting tool that is IPKG I and IPKG II sheets. This study was conducted for 4 cycles. The results of the design of learning implementation plan obtained on average in the first cycle of 2.79, cycle II of 3.62, the third cycle of 3.76, IV cycle of 3.93, The results of the learning learning obtained on average on cycle I of 2.88, cycle II of 3.66, cycle III of 3.72, IV cycle of 3.86, The results of student learning outcomes obtained on average in the first cycle of 67.36, cycle II of 70 , 97, cycle III equal to 73,75, cycle IV equal to 94,44. Total number of students in cycle I reached 15 people happened in cycle II increase to 20 people then happened peningkatn on cycle III reached 22 people and in cycle IV happened improvement for all student class V A which amounted to 36 people. From the data obtained can be concluded that there is an increase in each cycle. Thus research using the type of Student Team Achievement Division can improve the learning outcomes Social Science class VA State Elementary School 04 Bengkayang Bengkayang District Bengkayang. Keywords: Improvement, Learning Outcomes, Social Studies, Student Team Type Achievemen                  Division